The Buddhist world-view - McLean, George F.; Singh, Raghwendra Pratap (Om Publications, 2001)
Contributed papers presented at the International Colloquium on "Hindu Spiritual Roots of Chinese Buddhism" held on Dec. 2-3, 1999 at Jawaharlal Nehru University, New Delhi.